The dynamic transcriptome during maturation of biofilms formed by methicillin-resistant Staphylococcus aureus - Vlaeminck, Jelle; Lin, Qiang; Xavier, Basil Britto; De Backer, Sarah; Berkell, Matilda; De Greve, Henri; Hernalsteens, Jean-Pierre; Kumar-Singh, Samir; Goossens, Herman; Malhotra-Kumar, Surbhi (Frontiers in Microbiology, 2022)
Methicillin-resistant Staphylococcus aureus (MRSA), causing chronic infections, forms prolific biofilms which afford an escape route from antibiotic treatment and host immunity. However, MRSA clones are genetically diverse and mechanisms underlying biofilm formation remain under-studied. Such studies form the basis of developing targeted therapeutics. Here, we studied the temporal changes in the biofilm transcriptome of three pandemic MRSA clones: USA300, HEMRSA-15, and ST239. Biofilm formation was assessed on a static model using one representative strain per clone. Total RNA was extracted from biofilm and planktonic cultures after 24h, 48h, and 72h of growth, followed by rRNA depletion and sequencing (Illumina Inc., NextSeq500, v2, 1x75bp). Differentially expressed gene (DEG) analysis between phenotypes and among early (24h), intermediate (48h), and late (72h) stages of biofilms was performed together with co-expression network analyses. To understand the influence of SCCmec and ACME on biofilm formation, isogenic mutants containing deletions of the entire elements or of single genes therein were constructed in USA300. Genes involved in primarily core-genome-encoded KEGG pathways (transporters, purine metabolism, and others) were up-expressed in 24h biofilms compared to 24h planktonic cultures. However, the number of affected pathways in the ST239 24h biofilm (n = 11) was remarkably lower than in USA300/EMRSA-15 biofilms (USA300: n = 27, HEMRSA-15: n = 58). The clfA gene, which encodes clumping factor A, was the single common DEG identified across the three clones in 24h biofilms (2.2- to 2.66-fold). In intermediate (48h) and late (72h) stage of biofilms, decreased expression of central metabolic and fermentative pathways (glycolysis/gluconeogenesis, fatty acid biosynthesis), indicating a shift to anaerobic conditions, was already evident in USA300 and HEMRSA-15 in 48h biofilms; ST239 showed a similar profile at 72h. Lastly, SCCmec+ACME deletion and opp3D disruption negatively affected USA300 biofilm formation. Our data shows striking differences in gene expression during biofilm formation by three of the most important pandemic MRSA clones, USA300, HEMRSA-15, and ST239. The clfA gene was the only significantly up-expressed gene across all three strains in 24h biofilms and exemplifies an important target to disrupt early biofilms. Our data indicate a critical role for arginine catabolizing pathways in early biofilm formation.